Evaluation and Design of a Tender Document Information System, Aceh Public Works Department - Hamdani; Mukhtar; Ihsanuddin (Journal Dekstop Application (JDA), 2022)
This study aims to evaluate and design an Auction Document Data Collection Information System at the Aceh Bina Marga Service. With the background of rapid development of information technology, there are still challenges in the effectiveness and efficiency of auction document data collection in the institution. The data collection method was carried out through field studies and literature studies. The results of the study indicate the need for the development of an effective and efficient information system to improve performance and competitiveness. The proposed system uses Visual Basic 6.0 as a development platform. This study is expected to contribute to improving auction document data management at the Aceh Bina Marga Service